Indonesia etc. exploring the improbable nation - Pisani, Elizabeth (W.W. Norton & Company, 2014)
An entertaining and thought-provoking portrait of Indonesia: a rich, dynamic, and often maddening nation awash with contradictions. Jakarta tweets more than any other city on earth, but 80 million Indonesians live without electricity and many of its communities still share in ritual sacrifices. Along the way, she observes Big Men with child brides, debates corruption and cannibalism, and ponders 'sticky' traditions that cannot be erased.